Hadith #5001 - Sunan Abi Dawud - Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'aib bin Ishaq bin 'Abdur Rahman شعيب بن إسحاق بن عبد الرحمن; Sulaiman bin 'Abdur Rahman سليمان بن عبد الرحمن بن عيسى; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yazid bin Sa'id bin Thamama (Sunan Abi Dawud)
The only reason why he asked whether the whole of him should come in was because of the smallness of the tent
Grade: Sahih